Bridging the Gap between Theoretical Learning and Practical Application: A Qualitative Study in the Italian Educational Context - Stefania Fantinelli; Michela Cortini; Teresa Di Fiore; Stefano Iervese; Teresa Galanti (MDPI AG, 2024)
In the contemporary educational landscape, there is a growing recognition of the transformative impact of practical experiences within traditional learning frameworks. This shift reflects a pedagogical evolution that values contextualized learning and the acquisition of practical skills together with theoretical knowledge. In the Italian educational context, School-Work Alternation (SWA) represents a proactive response to the evolving needs of the workforce and the imperative for educational institutions to prepare students for professional life. This study's objectives include a deep exploration of students' SWA experience, evaluating its impact on employability perceptions and the sense of agency, examining the influence of Self-Orientation, and contributing insights to the discourse on integrating practical experiences in education. Employing a mixed methodology and a bottom-up approach, 63 high school students of different Italian regions participated in an online in-depth interview and an ad hoc questionnaire designed to measure the experience of SWA in relation to variables of interest, utility, advantage, perception of support, quality of received mentoring, engagement, and satisfaction. The quantitative results indicate that personal choice significantly influences the perceived usefulness of and satisfaction with SWA, with those students guided by curiosity exhibiting higher utility and satisfaction. Qualitative analysis underscores both positive and negative aspects, with respondents viewing SWA as a useful experience bridging work, corporate, and school realms provided that students are key players in the SWA experience's choice and that the SWA's partners are motivated to guide them in this practical training. Moreover, results highlight SWA's relevance in guiding academic and career paths, emphasizing its potential to offer valuable support to students. This study contributes nuanced insights into integrating practical experiences in education, offering recommendations for educators and policymakers to better prepare students for the dynamic demands of the modern job market.